Assessment of public literacy in TB prevention and control in the National 13th Five-Year plan for Tuberculosis Prevention and Control (2016–2020) in China - Shuaihu Ni; Gang Chen; Jia Wang; Yuhong Li; Hui Zhang; Yan Qu; Yanlin Zhao; Xiaofeng Luo (BMC Health Services Research)
Abstract Background China has always been a country with a high burden of tuberculosis. In order to end TB, the Chinese government launched three plans for TB prevention and control. The Chinese government implemented the National 13th Five-Year plan for Tuberculosis Prevention and Control (2016–2020) to promote TB prevention and control from policy, technology, health promotion and other aspects from 2016 to 2020. The objective of this study was to assess public TB literacy in health promotion in the National 13th Five-Year plan for Tuberculosis Prevention and Control (2016–2020), and provide a basis for the next plan. Compared with previous studies on TB literacy, this study increased the sample size to cover all provinces in China, which is more representative. Methods A cross-sectional study covering all provinces in China was conducted in 2020. 47,728 questionnaires were collected. Logistic regression was used to analyze the overall awareness of TB health literacy among people with different demographic characteristics. Multicollinearity and outliers were checked using VIF and box plots, respectively. Results In the TB key information, the total awareness rate of TB key information was 82.51%. Participants had poor awareness that TB is a chronic infectious disease, and if the whole course of treatment is standardized, the vast majority of patients can be cured and can avoid infecting others. Participants who received public education on TB had better awareness of TB key information. Participants who were over 60 years old, had a primary school or below degree, students, and did not receive public education on TB were less likely to know all TB key information. In the public education methods, participants were more likely and preferred to receive public education on TB through television or radio (67.93%) and Internet (33.85%) more and preferred television or radio (65.39%) and Internet (54.60%). Compared with participants aged below 60, participants aged 60 and above were more likely to receive public education on TB through relatives or friends (16.80%) (P < 0.001) and preferred to receive public education on TB through television or radio (68.15%), doctor consultation (42.19), relatives or friends (16.15%) (P < 0.001). Participants were more likely to query health-related information through self-media platforms (41.55%) and search engines (31.41%) on the Internet, but the elderly (60 years old and above) and participants with primary school or below degree were more likely to not to query health-related information (56.27%, 59.30%) on the Internet. In the public education materials, participants preferred audiovisual (40.69%), text and images (39.51%) public education materials. Participants preferred video (60.12%), text and image (51.78%) health-related information on the Internet. Conclusions The overall public TB literacy was considered high, but the awareness of some TB key information did not reach the target, and it is necessary to strengthen public education on TB for the elderly, people with low education and students. In the future, audiovisual media and the Internet should be the main methods of public education on TB for all people. Relatives or friends dissemination and doctor consultation are also suitable public education methods for older people. More health-related information should be promoted on the Internet, especially on self-media and search engine. TB public education materials and health-related information should use more audio-visual types.